Revealing Students’ Responses on the Use of Flipgrid in Speaking Class: Survey on ICT - syahrizal, Trisnendri; Pamungkas, Mundriyah Y (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2021)
Along with the development of the 4.0 era, the use of ICT media is not a new thing in the world of education. Many previous studies have integrated various technology-based media (ICT) with language learning including speaking lessons. One of the platforms that is currently being widely used is FLIPGRID. The main objective of this research is to reveal how students respond to the use of FLIPGRID as an ICT-based media that focuses on Speaking. The research method used is the qualitative method. The instruments used in this study were questionnaires and interviews. From the results of the study, it was found that there were 26 variants of positive responses from the accessibility, internet connectivity, psychological fulfillment, the interactive features, and 16 variants of negative responses of students to the use of the Flipgrid application ranging from competitiveness, equipment, and originality. The most positive responses that arise are that this application is easy to use, while the most negative responses that arise are difficulties or the upload process is quite long. It can be concluded that the FLIPGRID application has more positive responses than negative responses so that this application can be used by teachers and lecturers in the speaking class.